Psychopathy as a descriptive construct of personality among offenders - Haapasalo, Jaana (1992)
The study was based on the classical description of psychopathy by Hervey Cleckley. The principal goals of the work were (1) to examine various assessment methods used in psychopathy and their interrelationships, (2) to group offenders on the basis of assessment methods, and (3) to clarify the nature of criminal behavior among the Cleckley psychopaths and other offenders. 92 male offenders, aged 21 - 53 yrs and convicted of property, narcotics and traffic offenses, participated in the study. They completed psychopathy-related questionnaires (Eysenck Personality Questionnaire, MMPI Pd and Ma, CPI So, Zuckerman's Sensation Seeking Scale) and were assessed with the Psychopathy Checklist on the basis of file and interview data. Eysenck's and Zuckerman's questionnaires were first standardized in a sample of 967 respondents, aged 17 - 71 yrs. The results revealed two Checklist factors. Factor 1 included the core personality characteristics of the Cleckley psychopath. Factor 2 related to chronically unstable and antisocial lifestyle. The factor scores were correlated with the personality questionnaire scores, resulting in differential correlative patterns. The psychopaths were differentiated from the others by using global interview impressions, the Checklist total scores and a clustering of the Checklist items. Criminal behavior was examined by analyzing types of offense in the Checklist groups and by comparing the clusters with respect to four criminality variables. It is argued that Cleckley psychopaths can be discerned among the Finnish offenders and that psychopathy assessments should be based on similarities in the Checklist items between subjects rather than other methods.